The Algorithm of Decision Making During Off-Pump Coronary Artery Bypass Grafting - A. Mazur; P. Gurin; M. Babich; A. Borisenko (Ukrainian Journal of Cardiovascular Surgery, 2019)
Introduction. Over the past 20 years, both in Ukraine and in the world, the number of coronary artery bypass grafting (CABG) surgical procedures has shown significant increase. Complete exposition of coronary arteries in multivariate damage is possible only with the dislocation of the heart from physiological position in case of the use of stabilization systems (vacuum or compression). Therefore, hemodynamic disorders are the most common manifestations during off-pump CABG and are most pronounced when the circumflex branch of left coronary artery (LCA) and the distal branches of the right coronary artery (RCA) are shunted. This is manifested in lowering the cardiac index (CI), blood pressure (BP), changes in pulmonary artery pressure (PAP), central venous pressure (CVP) and saturation of mixed venous blood (SvO2). Therefore, the choice of the optimal solution during off-pump CABG (changing the mode of infusion therapy, the use of sympathomimetics or vasoconstrictors and their combination, etc.) in case of systemic hypotension remains an unresolved problem.Materials and methods. The study was based on a prospective analysis of surgical interventions (off-pump CABG) performed in patients from January 2015 through March 2017. Following the development of an optimized decision-making algorithm during off-pump CABG in order to confirm its effectiveness, a comparative analysis was performed with a group of patients who had performed an off-pump CABG without using this algorithm. Patients were divided into two groups: group 1 (study group, 40 patients) included patients who had optimized decision-making algorithm in the intraoperative period on the basis of a complex analysis of the factors leading to hemodynamic disorders during off-pump CABG: CI, PAP, BP, SvO2; group 2 (comparison group, 35 patients) included patients who underwent hemodynamic repair, focusing mainly on BP values.Results and discussion. The most marked violations of hemodynamics were observed in the formation of distal anastomoses between the aorta and the RCA and circumflex branch of the LCA. This was manifested in the decrease in CI and BP, and, in some cases, SvO2. The value of systemic vascular resistance (SVR) at the stages of the formation of distal anastomoses was below 800 dyn*sec*cm–5. Therefore, with the decrease in CI and BP in patients of group 1, norepinephrine was used at the dose of 50–150 ng/kg/min. This allowed to increase the mean BP above 80 mmHg and CI above 2 l/min/m2. In patients of group 2 with decreased BP, dopamine infusion was used at a dose of 6–9 μg/kg/min, which in 29% of cases caused tachycardia (> 100 bpm), which was not desirable during the distal anastomosis overlaying stages. Control of infusion with PAP allowed to reduce the total volume of intraoperative infusion (2402 ± 578 ml vs 2897 ± 635 ml, p = 0.0007) and reach intraoperative fluid balance (1235 ± 352 ml vs 1641 ± 419 ml, p = 0.0002). Patients in group 1 showed significantly shorter length of stay at the intensive care unit (ICU) and in hospital after the surgical intervention.Conclusions. The optimized decision-making algorithm during off-pump CABG has allowed to reduce intraoperative infusion therapy, as well as shorten the length of stay at ICU and duration of hospitalization.